2018
DOI: 10.1111/spc3.12429
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing cumulative dehumanization: An embodied praxis of “becoming” and resisting state‐sanctioned violence

Abstract: This paper introduces a new conceptual framework referred to as “cumulative dehumanization” to better understand the ways in which dehumanization penetrates individual and collective bodies and minds, cutting across policy and ideology and accumulating materially and affectively over time and space. Cumulative dehumanization illuminates a web of vertical and horizontal, synthetic, and dynamic processes that result in an ongoing racialized, state‐sanctioned dehumanization that is fundamentally cumulative—both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Therefore, in neighborhoods with high stop-and-frisk rates, the sociopolitical access to parks may be limited and should be further explored in prospectively designed studies. The significant stopand-frisk finding can also be supported by studies in procedural and social justice: police harassment hinders low-income people of color's social access to public spaces (39,40). The literature warns that the consequences of such policing practices on a neighborhood's social fabric go well beyond constraining use of public spaces; such practices can make communities of color feel dehumanized and excluded socially and spatially (39,40,64).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, in neighborhoods with high stop-and-frisk rates, the sociopolitical access to parks may be limited and should be further explored in prospectively designed studies. The significant stopand-frisk finding can also be supported by studies in procedural and social justice: police harassment hinders low-income people of color's social access to public spaces (39,40). The literature warns that the consequences of such policing practices on a neighborhood's social fabric go well beyond constraining use of public spaces; such practices can make communities of color feel dehumanized and excluded socially and spatially (39,40,64).…”
Section: Discussionmentioning
confidence: 97%
“…Elsewhere, limited research has shown that collective efficacy may be positively associated with park use (38). Lastly, order maintenance policing measures such as Terry stops or stop-and-frisk (stops on grounds of "reasonable suspicion, " at the discretion of police officers) are known to impact the use of public spaces in low-income neighborhoods (39,40) but have not been examined in relation to park use.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually it grows from Black feminist criminological traditions, what Hillary Potter frames as "intersectional criminology" (2015). It echoes the somatic geographies of embodied carcerality, liminal sites of diffuse connectedness (Moran 2013) and the potential "cumulative dehumanization" that happens from embodied violence (Bustamante, Jashnani, and Stoudt 2019). It engages with the overlay of kinship and prison, which Manuela da Cunha (2008) argues creates hypertotal institutions.…”
Section: Penaealogy As Theory: Critical Criminology and Learning Frommentioning
confidence: 96%
“…It is no secret that welfare reform tightened labor markets in poor neighborhoods. Even the section on the sociological work on dehumanization in Misdemeanorland , which I applaud, could acknowledge the deeply rooted structural and institutional nature of dehumanization in policing practices, specifically broken windows policing (see Bustamante, Jashnani, and Stoudt ). Last, I would also suggest that the sociological analysis ought to provide a more forceful critique of white supremacy as a core driver of the overarrest and criminalization of black and brown bodies.…”
mentioning
confidence: 99%